Kinetics of the complete combustion of dilute propane and methyl ethyl ketone over Cr-doped ZrO2 catalyst - Choudhary, Vasant R.; Deshmukh, G. M. (Chemical Engineering Science, 2005)
The kinetics of the complete combustion of propane and methyl ethyl ketone (MEK) at very low concentration in air (0.45 and 0.4 mol% in air, respectively) over Cr-doped ZrO2 (cubic) catalyst (Cr/Zr = 0.25) at different temperatures (485-673 K) in the kinetic control regime have been investigated. The combustion rate data could be fitted well to both the power law and redox (Mars-Van Krevelen) models. From the power law model, the apparent activation energy for the combustion of propane and MEK has been found to be 16.5 and 13.2 kcal mol(-1), respectively. Among the two models, the redox one, however, gave a better fit to the kinetic data for both the combustion of propane and MEK. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: combustion kinetics; combustion of methyl ethyl ketone; combustion of propane; Cr-doped ZrO2 (cubic) catalyst; methyl ethyl ketone; propane

Performance assessment of HC-290 as a drop-in substitute to HCFC-22 in a window air conditioner - Devotta, S; Padalkar, AS; Sane, NK (International Journal of Refrigeration - Revue Internationale Du Froid, 2005)
As per the Montreal Protocol, CFCs and HCFCs are being phased out. HCFC-22 is used in window air conditioners. This paper presents the experimental performance study of a window air conditioner with propane (HC-290), a natural refrigerant, as a drop-in substitute to HCFC-22. Experimental results showed that HC-290 had 6.6% lower cooling capacity for the lower operating conditions and 9.7% lower for the higher operating conditions with respect to HCFC-22. The coefficient of performance for HC290 was 7.9% higher for the lower operating conditions and 2.8% higher for the higher operating conditions. The energy consumption of the unit with HC-290 was lower in the range 12.4-13.5% than HCFC-22. The discharge pressures for HC-290 were lower in the range 13.7-18.2% than HCFC-22. For HC-290, the pressure drop was lower than HCFC-22 in both heat exchangers. This paper also presents simulation results for the heat exchangers of an HCFC-22 window air conditioner with HC-290 as a drop-in substitute. The simulation has been carried out using EVAP-COND, a heat exchanger model developed by NIST [National Institute of Standards and Technology. EVAP-COND: simulation models for finned-tube heat exchangers, Maryland, USA (2003). http://www2.bfrl.nist.gov/software/evap-cond/ [18]]. The simulated evaporator capacities are within +/- 4% of the experimentally measured cooling capacities for both refrigerants. Simulation results for HC-290 and HCFC-22 are compared. The exit temperatures of HC-290 are lower by 0.3-1.2 degrees C in the condenser and are higher by 2.1-2.4 degrees C in the evaporator than HCFC-22. Evaporating pressures of HC-290 are lower by 2.1-3.3% as compared to HCFC-22. The pressure drops of HC-290 are lower in both the evaporator and the condenser as compared to HCFC-22. The outlet temperatures of air for HCFC-22 and HC-290 in both heat exchangers are nearly the same. (c) 2005 Elsevier Ltd and IIR. All rights reserved.
Keywords: air conditioner; COP; Evaporator; experiment; performance; propane; R-22; simulation; window

Sites for CO2 activation over amine-functionalized mesoporous Ti(Al)-SBA-15 catalysts - Srivastava, R.; Srinivas, D.; Ratnasamy, P. (Microporous and Mesoporous Materials, 2006)
{Activation of CO and its utilization in the synthesis of chloropropene and styrene carbonates over functionalized, mesoporous SBA-15 solids, have been investigated. The surface basicity of SBA-15 was modified with nitrogen-based organic molecules of varying basicity viz., alkyl amines (-NH2), adenine (Ade), imidazole (Im) and guanine (Gua). The surface of SBA-15 was also functionalized with Ti4+ and Al3+ species. The acid-base properties of these modified SBA-15 materials were investigated by temperature-programmed desorption (TPD) and diffuse-reflectance infrared Fourier transform (DRIFT) spectroscopy. NH3 and pyridine were used as probe molecules for acid sites, while CO, was used to characterize the basic sites. CO was activated at the basic amine sites forming surface carbamate species (IR peaks: 1609 and 1446 cm(-1)). The latter reacted further with epoxides adsorbed on the acid sites forming cyclic carbonates. A correlation between the intensity of the IR peak at 1609 cm(-1) and cyclic carbonate yield has been observed. The cyclic carbonate yields were higher when both the acid and base functionalities were present on the surface. The Ti- and Al-SBA-15 functionalized with adenine exhibited the highest catalytic activity and selectivity. There is an optimal dependence (''
Keywords: aromatization; Ga-based zeolites; propane; Si/Al ratio; Si/Ga ratio; zeolitic factors

Unprecedented two-dimensional polymeric [Zn(OOC-C6H4-COO)(2)](2_)(n)[+H3N-(CH2)(3)-NH(3])(+)n system bearing one-dimensional chain of zinc(II) bis(phthalate) dianions held by propane-1,3-diammonium cations: crystal structure, thermal and fluorescent pr - Padmanabhan, A.; Joseph, K. C.; Puranik, Vedavati G.; Huang, Xiaoying; Li, Jing (Solid State Sciences, 2007)
A novel zinc(II) phthalate compound, [Zn{C6H4(COO)(2)}(2)](n)(2-)[NH3-(CH2)(3)-NH3](n)(2+), 1 Which contains four different phthalate moieties coordinated to the Zn(II) ion through one each of their carboxyl ate moieties in a eta(1)-form and each phthalate moiety acting as a bridging unit with an overall tetrahedral geometry around the metal ion has been prepared and structurally characterized. The structure is unique in the sense that the dianionic moieties [Zn{C6H4(COO)(2)}(2)](2-) form an infinite one-dimensional network composed of 14-membered cyclic units interconnected in a way that they are disposed alternatively in almost perpendicular planes. The dicationic [NH3-(CH2)(3)-NH3](2+) units are seen to hold these one-dimensional chains by strong coulombic and hydrogen bond interaction, resulting in an infinite two-dimensional layered structure of 1. The compound is thermally stable up to 250 degrees C. Above this temperature it loses one equivalent of phthalate moiety along with the diammonium unit to yield Zn(II) phthalate. The thermodynamic and kinetic parameters associated with this process could be evaluated using Coats-Redfern equation which shows the activation energy Ea for the process as 305.0 kJ mol(-1), the frequency factor A as 1.49 x 10(11) s(-1) and the entropy change Delta S as -35.90 JK(-1) mol(-1). Fluorescent emission properties of 1 was studied by exciting the compound at 380 nm and also at 322 nm which were found to be the two lambda(max) corresponding to absorptions of the molecule. Interestingly, the compound gave same type of emission spectra showing a maximum around 444 nm on exciting at these two different wavelengths, indicating that the molecule comes to the first excited state from the higher excited state by a fast non-radiative process before it exhibits singlet emission to come to the ground state. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: 1; 3-diammonium; cyclic chain; fluorescent emission; layered structure; propane; zinc(II) bis(phthalate) dianion; zinc-phthatate